2.14 mW deep-ultraviolet laser at 165 nm by eighth-harmonic generation of a 1319 nm Nd:YAG laser in KBBF. (21st January 2016) - Dai, Shi-Bo; Chen, Ming; Zhang, Shen-Jin; Wang, Zhi-Min; Zhang, Feng-Feng; Yang, Feng; Wang, Zhi-Chao; Zong, Nan; Liu, Li-Juan; Wang, Xiao-Yang; Zhang, Jing-Yuan; Bo, Yong; et al.
Abstract: We report a nanosecond (ns) 165 nm deep-ultraviolet (DUV) laser with a maximum average power of 2.14 mW by eighth-harmonic generation (EHG) of a homemade ns 1319 nm Nd:YAG laser. The EHG was performed by cascaded second-harmonic generation (SHG) through successive stages of two LiB3 O5 crystals and one KBe2 BO3 F2 crystal. The generated radiation at 165 nm is the shortest DUV wavelength ever generated through SHG method and the highest average power of all solid state lasers below 170 nm to our knowledge. Such a ns DUV laser at 165 nm is of great interest for photoemission spectroscopy and Raman spectroscopy.